Android application for assembly instruction in augmented reality setting - Kusuma, Adi Hartanto (2018)
The purpose of the project is to develop an AR application in Android settings for assembly instruction using 3D model-based marker. It will also observe the effectiveness of the tracker to assembly process based on the result provided. In this project, Unity software is used with the plugin from Vuforia AR SDK that just released a 3D model target feature. Based on the result produced, the observation of the detection system shows that it is not reliable. Several factors and limitations are found to affect the detection rate of the tracker.